12(x-8)=12(x-11)-6

Simple and best practice solution for 12(x-8)=12(x-11)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(x-8)=12(x-11)-6 equation:



12(x-8)=12(x-11)-6
We move all terms to the left:
12(x-8)-(12(x-11)-6)=0
We multiply parentheses
12x-(12(x-11)-6)-96=0
We calculate terms in parentheses: -(12(x-11)-6), so:
12(x-11)-6
We multiply parentheses
12x-132-6
We add all the numbers together, and all the variables
12x-138
Back to the equation:
-(12x-138)
We get rid of parentheses
12x-12x+138-96=0
We add all the numbers together, and all the variables
42!=0
There is no solution for this equation

See similar equations:

| 3(x-3)=4x+8 | | x/95=162/20 | | 5(-x+2)=13-4(3x-1)= | | 2x-4(x-4)=3x+10-5x+6 | | 9x+5=11+7(x-3) | | 9y=4+5 | | 3m-11=16 | | u2-2/3u+5=0 | | 6x+3=-2x+19 | | 4-2(v-60)=-8 | | 4-2(v-60=-8 | | 2(4h+)=9h-2 | | -8(7+9x)=16 | | -17=3p-5 | | 3(n=5)+2=26 | | 22-6x=24 | | 45/12=30/n | | 4(2x+1)=3x+11 | | -3.7w=155.4 | | (x^2+12)/(x^2-9)=0 | | 63.1=6.1=(0.38)x15 | | 14/21=35/n | | 6x+2-3x=x+7+2x | | x^2+12/x^2-9=0 | | 6x+2-3x=x+72x | | -6x-6(2x-16)=6 | | 2/3=35/n | | 1-(3/8)x=0 | | 8x-5=5-8x | | 45x=211 | | 63.1=6.1-(.08)x(15) | | 4+12x=9x+16 |

Equations solver categories